2012
DOI: 10.1038/nprot.2012.127
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness-controlled three-dimensional extracellular matrices for high-resolution imaging of cell behavior

Abstract: Regulation of cell functions by the physical properties of the extracellular matrix (ECM) has emerged as a crucial contributor to development and disease. Two specific physical properties of the ECM, stiffness and dimensionality, each influence cell signaling and function. As these ECM physical properties are linked to other properties that also regulate cell behavior, e.g., integrin ligand density, parsing the specific contributions of ECM stiffness and dimensionality has proven difficult. Here we detail a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 75 publications
2
162
0
1
Order By: Relevance
“…The moduli of additional A and B combinations are reported in the literature. 17,25,26 The gel stiffness of fully swollen gels was measured by rheology (AR 2000ex rheometer, TA Instruments) with a 20 mm upper parallel geometry, oscillatory frequency sweep test 1 -10 Hz, and 2% constant strain. As anticipated, it was demonstrated that both storage modulus, G', and loss modulus, G", are independent of frequency ( Figure 2B).…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moduli of additional A and B combinations are reported in the literature. 17,25,26 The gel stiffness of fully swollen gels was measured by rheology (AR 2000ex rheometer, TA Instruments) with a 20 mm upper parallel geometry, oscillatory frequency sweep test 1 -10 Hz, and 2% constant strain. As anticipated, it was demonstrated that both storage modulus, G', and loss modulus, G", are independent of frequency ( Figure 2B).…”
Section: Representative Resultsmentioning
confidence: 99%
“…Polyacrylamide allows manipulation of substrate stiffness to encompass the stiffness of all soft tissues in the body (0.3 -300 kPa) 1 with a simple change in polymer precursor concentration (Figure 2, Table 1, also see references 17,25,26 ). Coupled to the fact that PA gels are fairly inexpensive and simple to prepare, they have become indispensable platforms in the study of stiffness-dependent cell-material interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugating visibly transparent ECMs and polyacrylamide substrates of amenable compliance with microscopic studies will allow for cell-ECM engagement studies such that endothelial cell vascular angiogenesis can be monitored with high spatial and temporal resolution. These types of experimental approaches have already begun to reveal important differences in endothelial cell shape, polarity, migration, and the effects of proteins that regulate these processes 5,31,90 . Future efforts should aim to identify how the combination of ECM compliance and dimensionality mechanosensing may serve to locally control proteins that target and regulate cytoskeletal dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The cells are able to distinguish between different topographies in due their capability to sense dimensionality [1]. Based on the natural extracellular matrix (ECM) structure, substrate topographies can be designed as an important signaling modality to direct cell fate [2].…”
Section: Introductionmentioning
confidence: 99%